Non prioritized belief revision with ansprolog - Simari, Gerardo I. (2004)
One of the key aspects in the design of an architecture for autonomous agents is the way in which beleifs are revised in the face of new information. An intelligent agent must be prepared to handle new information (be it sensory input, communication with other agents, etc). The areas of Knowledge Representation and Reasoning and Belief Revision deal with the issues of how beliefs are represented, how they are used in reasoning processes, and how a current body of beliefs reacts to the appearance of new information. There are many problems that must be solved in order to e®ectively manage a body of knowledge which, more often than not, may be incomplete or even inconsistent. The adequate solution to these problems is an essential feature of autonomy, because an agent must always be up to date in order to behave accordingly.